Presenting Oneself as a Nurse: A Social and Professional Reality Construction - Ojo, A.A.; Mutea, Naomi K.; Wambui, T.; Chelagat, D. (Unisa Press, 2002)
The paper examined the historical development of nursing education and practice in two selected African countries as a background for analysing the image of nurses and nursing. Mead's (1934) Symbolic InteractionistTheof\' was employed to describe the basis of nurse;' low social and professional image which has been perpetuated by feminization of nursing, its classification as a low status occupation, its consignment as an appendage of medicine and widespread discrimination against womcn in Africa. Since reality construction is a continual creation as individuals interact in any social situation and as the social status and professional roles of nurses improve the image and self presentation will be enhanced. The submissive, accepting and passive doer-oriented critical mass of practising nurses in these countries cxplains the need for expanding degree programmcs that will facilitate collegiality in clinical relationships. It is argued that liberal university education is an important prerequisite for nurses to effectively use the concepts of assertiveness, power and influence to bring about positive change in their image and provision of quality nursing care. Recommendations made include need for nurses to convey messages of maturity, responsibility and expertise to patients, relatives and other stakeholders in health care services through their appearance, language, behaviour and performance of their professional responsibilities.
Keywords: Company of equals; Institutional property; Multiple cadres of nurses; Nurses' image; Presenting self; Reality construction